Are outcomes for childhood leukaemia in Australia influenced by geographical remoteness and Indigenous race?. Issue 4 (9th February 2021) - Jessop, Sophie; Ruhayel, Sandra; Sutton, Rosemary; Youlden, Danny R.; Pearson, Glenn; Lu, Cynthia; Milne, Suzanne; Henderson, Michelle J.; Aitken, Joanne F.; Kotecha, Rishi S.; Revesz, Tom
Abstract: Background: Presenting features, biology and outcome for childhood leukaemia are known to vary by ethnic origin, geographic location and socioeconomic group. This study aimed to compare presentation patterns, follow‐up and clinical outcomes in Indigenous and non‐Indigenous children with acute leukaemia in Australia, and to assess the impact of remoteness and area‐based socioeconomic disadvantage on outcome. Methods: A retrospective review of children aged between 1 day and 18 years who were diagnosed with acute leukaemia in South Australia (SA), Northern Territory (NT) and Western Australia (WA) between 2009 and 2018 was performed. Data were collected from children treated at the Women's and Children's Hospital, Adelaide and Perth Children's Hospital. Results: Analysis of 455 children treated for acute leukaemia showed that children from remote/very remote localities had inferior overall survival ( p  = .004). Five‐year overall survival was 91.7% (95% CI: 87.9–94.3%) for children with acute lymphoblastic leukaemia (ALL) and 69.8% (56.7–79.5%) for acute myeloid leukaemia (AML). A larger proportion of Indigenous children from SA/NT were diagnosed with AML compared to non‐Indigenous children (60.0% vs. 14.4%, p  = .001). Indigenous children were less likely to be enrolled on clinical trials (34.5% vs. 53.1%, p  = .03) and more likely to be lost to follow‐up (26.1% vs. 9.2%, p  = .009). Conclusion: Geographic remoteness of residence is associated with inferior overall survival for Australian children with leukaemia. Indigenous children with acute leukaemia suffer from disparities in outcomes. These findings provide evidence to guide national policy in supporting appropriate resource allocation to overcome the challenges faced by children within these groups.